Analisis Penanganan Cargo Outgoing terhadap Kelancaran Operasional Pada Terminal Kargo PT Angkasa Pura 1 Balikpapan - Anri yani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
The data analysis tool used is an interview that describes an object of research in its true state. This study aims to explore facts which are then described with guidelines on the question items in observation, interviews and field documentation. Data collection techniques using observation, interviews, documentation, and literature. The results of the analysis show that the handling of outgoing cargo starting from acceptance, weighing goods, making documents (documentation, marking, labeling & x-tray cargo, storage, build-up and loading, is smooth, but there are several things that must be considered, namely every year. Outgoing cargo increases the number of employees and employees must pay more attention to the existing SOP in order to minimize the obstacles that will occur. It is hoped that this research can become a better input for the handling of outgoing cargo to the smooth operation of outgoing cargo handling.